ANALYSIS OF THE PHENOMENON OF ONLINE SCAMS IN ONLINE JOB SEARCHES SYNDICATED WITH TRAFFICKING CRIMES INTERNATIONAL LAW PERSPECTIVE - Ulfah, Qorry (NOMOI Law Review, 2024)
This research is interesting to discuss because of technological developments that give rise to the occurrence of Online scams carried out in terms of offering foreign workers through job vacancies advertised by utilizing social media pages. The problem in the study is related to the criminal responsibility of the country perpetrating online scams according to international law. and related to the extent of intervention of the country of origin of sending labor to the country of online scam perpetrators legally. The type of research used in the form of normative juridical research is sourced from secondary data through data processing from primary legal materials, secondary legal materials and tertiary law. Based on the results of research in trafficking in persons , International Law provides policies to States parties in taking steps to implement the law through arrangements in the States of the Parties based on agreed conventions, one of which is through protocols to prevent, prosecute, and punish trafficking in persons, especially women and children (United Nations Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially Woman and Children). Located in Italy, the United Nations formulated the Palermo Protocol and related interventions were carried out by means of international cooperation that could include the exchange of information, training, and technical assistance between countries.